2014
DOI: 10.1675/063.037.0202
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Reddish Egret (Egretta rufescens) Diet During the Breeding Season Across its Geographic Range

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This was the case in the Florida Everglades where nest success of great egrets and white ibises (Eudocimus albus) is lower in years with below average prey availability as compared to years with high prey availability (Herring et al, 2010). Prey availability was not examined in this study; however, sheepshead minnow has been identified as a major prey item of reddish egrets breeding in Texas (Holderby et al, 2014) and the habitat of sheepshead minnow largely coincides with the foraging habitat of reddish egrets, that is, shallow water with minimal vegetation. Therefore, foraging habitat availability is likely related to prey availability.…”
Section: Discussionmentioning
confidence: 97%
“…This was the case in the Florida Everglades where nest success of great egrets and white ibises (Eudocimus albus) is lower in years with below average prey availability as compared to years with high prey availability (Herring et al, 2010). Prey availability was not examined in this study; however, sheepshead minnow has been identified as a major prey item of reddish egrets breeding in Texas (Holderby et al, 2014) and the habitat of sheepshead minnow largely coincides with the foraging habitat of reddish egrets, that is, shallow water with minimal vegetation. Therefore, foraging habitat availability is likely related to prey availability.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, these results do not offer evidence that reddish egrets possess any particular resilience to coastal disturbances compared to other waterbird species. In fact, due to the specialized aspects of their life history, relying on shallow flats and lagoons to hunt small fish (Lowther & Paul 2002, Holderby et al 2014, reddish egrets may be especially vulnerable to the habitat alterations currently impacting the species' range (Green et al 2011). As coastal development in the Gulf of Mexico increases, due to human populations growing and shifting toward coastal areas (Cendrero & Fischer 1997), habitat is gradually being replaced by man-made structures (Leu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As a gregarious species, individuals of both morphs may benefit from their diverging cognitive strategies and make them better prepared for environmental change, which could improve survival and population persistence. Moreover, since the polymorphism exists across the entire species' distribution, i.e., is not restricted to a mixing zone where the two morphs meet as in many other polymorphic species (e.g., Roulin, 2004;Holderby et al, 2014), individuals may benefit from associating with different morphs. This supports Forsman et al (2008) who proposed that polymorphic species are better prepared for environmental change due to the existence of different behavioral strategies.…”
Section: Novelty Responses To Open and Dense Habitatsmentioning
confidence: 99%